Factors related to sinus rhythm at discharge after radiofrequency ablation of permanent atrial fibrillation in patients undergoing mitral valve surgery - Rostagno, Carlo; Gelsomino, Sandro; Capecchi, Irene; Rossi, Alessandra; Montesi, Gian Franco; Stefàno, Pier Luigi (Heart and vessels, 2016)
Late recovery of sinus rhythm is unusual in patients with permanent AF treated by (radiofrequency) RF maze procedure during mitral valve surgery. Identification of clinical and instrumental preoperative factors predictive of early success of RF ablation in patients with permanent AF undergoing mitral valve surgery may improve selection of subjects to obtain long-term results. Hundred and thirty consecutive patients with permanent AF and mitral valve disease underwent modified RF maze procedure during concomitant mitral valve surgery. Rheumatic valve disease (61 pts) and mitral valve prolapse (41 pts) were the more common aetiology of valve abnormalities. Mitral valve replacement was performed in 54 % of patients and mitral valve repair in the remaining 46 %. Four patients died after surgery. At discharge, 87 patients (69 %) were in sinus rhythm (group 1) and 43 patients in AF persisted (group 2). At an average 24-month follow-up, sinus rhythm was present in 67 % of patients, and 33 % were in atrial fibrillation. In this period, late recovery of sinus rhythm was observed only in five patients, while eight discharged in sinus rhythm developed again atrial fibrillation. Among preoperative parameters at univariate analysis female sex, atrial fibrillation >24 months, left atrial diameter >54 mm, left atrial area >24 cm 2 , rheumatic valve disease and NYHA class were associated with persistence of AF. At Cox regression multivariate analysis, increased left atrial area (OR 1.07 per unit increase—95 % CI 1.01–1.131) and rheumatic aetiology of valve disease (OR 4.52, 95 % CI 1.65–12.4) were associated with persistence of AF at hospital discharge. Persistence of AF after RF ablation in patients undergoing mitral valve surgery is related to aetiology, e.g. rheumatic valve disease, and to increasing left atrial diameter. Due to low rate of late recovery of sinus rhythm, indication to RF ablation associated with MV surgery should be carefully considered in patients with large atria and rheumatic mitral valve disease.